2007
DOI: 10.1038/sj.jcbfm.9600527
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefits by Human Mesenchymal Stem Cells (hMSCs) and Ang-1 Gene-Modified hMSCs after Cerebral Ischemia

Abstract: Transplantation of human mesenchymal stem cells (hMSCs) prepared from adult bone marrow has been reported to ameliorate functional deficits after cerebral artery occlusion in rats. Although several hypotheses to account for these therapeutic effects have been suggested, current thinking is that both neuroprotection and angiogenesis are primarily responsible. In this study, we compared the effects of hMSCs and angiopoietin-1 gene-modified hMSCs (Ang-hMSCs) intravenously infused into rats 6 h after permanent mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(159 citation statements)
references
References 41 publications
6
149
2
2
Order By: Relevance
“…These observations are consistent with previous studies in which angiogenesis and neurogenesis were accelerated along with neurologic recovery in animal models of stroke after cell transplantation with MSCs [62] and HSCs [33]. In addition, we found that an increase in CBF correlated with reduction in locomotion during the light phase.…”
Section: Discussionsupporting
confidence: 93%
“…These observations are consistent with previous studies in which angiogenesis and neurogenesis were accelerated along with neurologic recovery in animal models of stroke after cell transplantation with MSCs [62] and HSCs [33]. In addition, we found that an increase in CBF correlated with reduction in locomotion during the light phase.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, transplanted MSC migrated to the neighborhood of the injured spinal cord, but did not differentiate into glial or neuronal elements. Current thinking is that the potential beneficial effects of MSC in SCI are not related to neuronal or glial differentiation of MSC, but rather from their secretion of growth factors and/or cytokines (Sasaki et al, 2009), which can provide neuroprotection (Chen et al, 2002;Parr et al, 2007), induction of axonal sprouting (Shen et al, 2006), neovascularization (Onda et al, 2008), and immunomodulation (Ohtaki et al, 2008;Bai et al, 2009). MSC may also promote axonal regeneration or encourage functional plasticity by establishing an environment that supports axonal growth, for example, by abrogating the inhibitory influence of the chondroitin sulfated proteoglycans (CSPG), and/or myelin debris present in the injury site and glial scar (Wright et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show that administration of MSC after a HI insult significantly reduces lesion volume, improves behavioral performance, and promotes neurogenesis. 35,[125][126][127] Furthermore, studies show that MSCs migrate to the ischemic boundary zone where they induce changes in brain environment that promote and support neurogenesis. [128][129][130] A study from our group showed that intracranial MSC treatment at 3 and 10 days after HI-induced injury changes the expression of genes involved in regenerative processes.…”
Section: Stem-cell Based Therapy: Enhancing the Neurogenic Potential mentioning
confidence: 99%